TINGKAT SERANGAN PENYAKIT BUAH KAKAO DI KOTA PAYAKUMBUH - Yudha, Pajri Ananta; Dwipa, Indra (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2024)
Cocoa is valuable crop for Indonesian foreign exchange. The research aimed to study the damage level of cocoa pod diseases in Payakumbuh. The research was conducted in cocoa plantation of Payakumbuh from November 2023 to January 2024. Survey method was used in the study and purposive random sampling was used to determine the sampling. The criteria to determine locations were ± 0.5 hectare of cocoa plantation and age of cocoa plant ± 4 years. According to criteria, 2 districts were chosen, Lamposi Tigo Nagari and Payakumbuh Timur. In each district, 5 sub-districts were chosen and in each sub-district, 2 cocoa plantations were chosen. The imaginary diagonal line was formed to determine the sampling plants. In each cocoa plantation, 10% of plants were determined for sampling or ± 400 plants. The result showed that 2 diseases were found in cocoa pod in Payakumbuh, cocoa pod rot and anthracnose. The percentage of attacked plant by cocoa pod disease was 20,45%, the percentage of attacked pod was 5,46% and attack intensity was 4,17%. For anthracnose disease, the percentage of attacked plant was 15,42%, percentage of attacked pod was 6,62% and attack intensity was 3,94%.